If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -8w = 2w + 9 Reorder the terms: 2 + -8w = 9 + 2w Solving 2 + -8w = 9 + 2w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-2w' to each side of the equation. 2 + -8w + -2w = 9 + 2w + -2w Combine like terms: -8w + -2w = -10w 2 + -10w = 9 + 2w + -2w Combine like terms: 2w + -2w = 0 2 + -10w = 9 + 0 2 + -10w = 9 Add '-2' to each side of the equation. 2 + -2 + -10w = 9 + -2 Combine like terms: 2 + -2 = 0 0 + -10w = 9 + -2 -10w = 9 + -2 Combine like terms: 9 + -2 = 7 -10w = 7 Divide each side by '-10'. w = -0.7 Simplifying w = -0.7
| -12/-9 | | k^2=-k | | 4.9t^2+8t-30=0 | | -(1-x)-[2x-(3-x)]=8 | | x^2-27*x=0 | | (x-3)(x+3)+5=0 | | 19-7=x/3 | | 1/4x-7/8x=10-50 | | (((x-5)/2)-((2x+5)/3))=(5/6) | | m+45=54 | | 3-6x=33+x | | 5x+21=12x-29# | | (((x-5)/2)-((2x-5)/3))=(5/6) | | 1/4x-7/8=10-50 | | 25x-29x=8-12 | | 2a+50=5a-4 | | x(x+4)+(x+4)= | | -4x-4x=18-2 | | 15+t=2 | | 3p+5q=36 | | 3x^3+23x-16x^2-6=0 | | A+12=26 | | -54+18=-4x+13x | | 81=9 | | 2(3x+5)+9=3x+34 | | 135=3y | | M/3+m/4=m/4 | | T=3a(ar+h) | | 161=7y | | 5-5=13x+7x | | 6y=114 | | 3n-14=17 |